The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/861234
|View full text |Cite
|
Sign up to set email alerts
|

Indium‐Nitrogen Codoped Zinc Oxide Thin Film Deposited by Ultrasonic Spray Pyrolysis on n‐(111) Si Substrate: The Effect of Film Thickness

Abstract: Indium-nitrogen codoped zinc oxide (INZO) thin films were fabricated by spray pyrolysis deposition technique on n-(111) Si substrate with different film thicknesses at 450°C using a precursor containing zinc acetate, ammonium acetate, and indium nitrate with 1 : 3 : 0.05 at.% concentration. The morphology and structure studies were carried out by scanning electron microscopy (SEM) and X-ray diffraction (XRD). The grain size of the films increased when increasing the film thickness. From XRD spectra, polycrysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Ye et al summarized the electrical properties of several types of group III (B, Al, Ga, and In)-N co-doped p-type ZnO thin films and found that the hole concentration density, Hall mobility, and electrical resistivity were in the ranges of 3 × 10 16 to 5 × 10 18 cm −3 , 0.1 to 15 cm 2 /V• s, and 0.015 to 2 × 10 2 Ω•cm, respectively [7]. The main considerations of the acceptordonor co-doping method for achieving ptype conduction in ZnO thin films are to lower the ionization energy of acceptors and donors, enhance the solubility of acceptor dopants [38], and reduce the self-compensation effect to create shallower acceptor levels (falling within the range of 0.1-0.2 eV above the valence-band maximum (VBM)). Various electrical parameters, including the carrier type, carrier concentration, Hall mobility, and electrical resistivity, of the ZnO-based semiconductor thin films, measured by Hall-effect measurement, are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Ye et al summarized the electrical properties of several types of group III (B, Al, Ga, and In)-N co-doped p-type ZnO thin films and found that the hole concentration density, Hall mobility, and electrical resistivity were in the ranges of 3 × 10 16 to 5 × 10 18 cm −3 , 0.1 to 15 cm 2 /V• s, and 0.015 to 2 × 10 2 Ω•cm, respectively [7]. The main considerations of the acceptordonor co-doping method for achieving ptype conduction in ZnO thin films are to lower the ionization energy of acceptors and donors, enhance the solubility of acceptor dopants [38], and reduce the self-compensation effect to create shallower acceptor levels (falling within the range of 0.1-0.2 eV above the valence-band maximum (VBM)). Various electrical parameters, including the carrier type, carrier concentration, Hall mobility, and electrical resistivity, of the ZnO-based semiconductor thin films, measured by Hall-effect measurement, are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Lately, efforts have been dedicated to the fabrication of modified ZnO nanocrystallites in order to enhance the structural, morphological, and optical properties of materials by modification of the surface properties, such as crystal deficiencies, electronic band gap, specific surface area, and O vacancies. Doping with nonmetallic elements such as carbon, nitrogen, and sulphur has also been considered to reduce the bandgap of ZnO semiconductors [8][9][10]. Specifically, carbon atoms have been usually employed as the dopant to change the morphological, structural, optical, and electronic properties of nano-ZnO because of the almost equivalent size with oxygen atoms.…”
Section: Introductionmentioning
confidence: 99%
“…The emission was observed after the carrier recombination. The carrier spatial transport ability depends on the environmental temperature [38,39]. The inconsistency of the BE band for samples measured at 10 K and room temperature suggests the non-uniformed BE-related defect distribution in the samples.…”
Section: Methodsmentioning
confidence: 99%